PENGARUH BERBAGAI PANJANG ENTRIES TERHADAP KEBERHASILAN SAMBUNG SISIP MANGGA (Mangifera indica L.) : BERBAGAI PANJANG ENTRIES TERHADAP KEBERHASILAN SAMBUNG SISIP MANGGA (Mangifera indica L.) - Ifa Nofita Dewi; Siswadi Siswadi; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study entitled The Effect of Various Lengths of Entries on the Success of Insertion of Mango (Mangifera indica L.). with the aim of knowing the effect of various lengths of entries on the success of insertion of mango (Mangifera indica L.). This research was carried out in November 2021 – January 2022 located at the Tohudan Food Crops and Horticulture Garden. This study used a single factor Completely Randomized Design (CRD) experimental design with treatments P1 (4 Cm), P2 (8 Cm), P3 (12 Cm), P4 (16 Cm), P5 (20 Cm). In this study there were 5 types of treatment with 5 replications, each type of experiment contained 2 plants so that there were a total of 50 plants. To determine whether there was an effect of treatment, this study used ANOVA analysis of variance data followed by DMRT test with a level of 5%. Parameters observed were the number of shoots, shoot length, number of leaves, stem diameter, and the success of insertion of finished seedlings. The results showed that the P4 (16 Cm) treatment gave the best grafting results compared to the other treatments.